New synonyms in Camellia (Theaceae): Camellia cucphuongensis, C. cylindracea and C. vidalii - Zhao, Dongwei (Phytotaxa, 2019)
Camellia cucphuongensis, C. cylindracea and C. vidalii are treated as heterotypic synonyms of C. flava, C. amplexicaulis and C. langbianensis, respectively.